Pemanfaatan Media Youtube Channel Jeda Nulis Dalam Membangun Sikap Toleransi Beragama Mahasiswa Komunikasi dan Penyiaran Islam Fakultas Dakwah dan KomunikasiUIN Sumatra Utara - Lanna Sari Rkt; Erwan Efendi (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
The purpose of this research is to describe how students of Islamic communication at the Faculty of Da'wah and Communication at the State Islamic University of North Sumatra use the media to foster an attitude of religious tolerance. Experts are interested in exploring this because virtual entertainment is increasingly modern, causing ministers to use new media to convey da'wah, where the target is young people, to be honest, students. Students who are supposed to be problem solvers hope that students are able to follow and apply firm resistance in public activities. The Faculty of Dakwah and Communication at the State Islamic University of North Sumatra is recruiting a number of communication and broadcasting majors for the 2022–2023 academic year and even semester for this qualitative study which uses a field analysis approach. Evidenced by the many students who re-uploaded Habib Ja'far's videos to their social media, students chose the YouTube channel to stop writing as a channel for listening to Islamic lectures because Habib's nature is calm, peaceful, and right on target. The research findings show that if students care about understanding religious tolerance, they also like to use the YouTube platform to listen to Islamic lectures. The obstacle experienced due to teaching through virtual entertainment is the problem of correspondence, because several parties cut the dai's recording and then changed it to create a new problem (slandering the dai's name). In this case, Dais might be able to add a timestamp to the video, which would be a workaround. Keywords: YouTube, Tolerance for Human Trafficking, Pause Writing, Habib Ja'far, and Students